Online mentoring of undergraduate medical students during COVID-19 pandemic in north Karnataka - Swati N. Tikare; Anita Deshpande; Raisa Kazi (Al Ameen Medical College, 2024)
Background: Students faced many challenges during online education during covid pandemic. Hence we planned to provide online mentoring program to first-year medical students of our college in this situation. This included mentoring regarding academic guidance and mental well-being. Aim and Objectives: This study aimed to obtain feedback from I professional MBBS students regarding the online mentoring program. Materials and Methods: A mentorship program was designed for MBBS First Professional students. 150 first-year students were mentored among which 94 students participated in the mentoring sessions. We used pre-validated questionnaire to obtain feedback. Results: The mentoring sessions were directed towards 150 first professional year students. Each session was attended by an average of 119.83 + 3.65 students in two batches. The feedback obtained from mentees showed the mentoring program increased their confidence, instilled interest in online education, reduced their stress and also helped to achieve the academic objectives. Conclusions: Online Mentoring program significantly addressed the student`s academic and social concerns. It instilled confidence, provided continuous motivation and kept the enthusiasm of mentees high to achieve their academic goals in the dreaded situation of pandemic.